NEUROPROTECTIVE EFFECT OF CINNAMON ACTIVE COMPOUNDS VIA ACTIVATION OF SIRT1: A MOLECULAR DOCKING APPROACH - Umi Kalsum; Husnul Khotimah; Nurfaizah Titisari Sulihah; Theakirana Firdaus; Fitrah Aulia Lisabilla; Editya Fukata; Happy Kurnia Permatasari; Sri Andarini (MNJ (Malang Neurology Journal), 2022)
Background: Neurodegenerative diseases are the main cause of morbidity and disability in the elderly. SIRT1 activation has been gaining popularity as novel treatment target. Cinnamon is known to possess neuroprotective abilities, however the mechanism in which it protects the brain is still limited. Objective: This research aimed to determine the interaction between several cinnamon active compounds with SIRT1 Methods: We used in-silico method to determine the molecular interactions between cinnamon main compounds as the ligands to target protein SIRT1. SIRT1 3D structure was retrieved from the Protein Data Bank and 4 ligands (Cinnamaldehyde, Caffeic Acid, Epicatechin, and Trigonelline) structures were obtained from PubChem web server, and we used Resveratrol as positive control ligand. SwissADME, Pyrx, Pymol, and Biovia Discovery Studio software were utilized in this research Results: All four ligands fulfilled Lipinski Rule of 5 criteria therefore they are suitable for oral administration. It was discovered in this study that epicathecin had higher binding affinity than the control ligand Resveratrol and interacted with SIRT1 in the similar amino acid residue as Resveratrol did. The binding pocket interaction between all ligands and SIRT1 are the same. Conclusion: Epicathecin, as one of the main cinnamon compounds, may possess neuroprotective properties by interacting with SIRT1. We pproposed that further research be implemented to investigate epicathecin biological effects on SIRT1 in vitro or in vivo.